Purified thick filaments from the nematode Caenorhabditis elegans: evidence for multiple proteins associated with core structures (The Rockefeller University Press, 1988)
The thick filaments of the nematode, Caenorhabditis elegans, arising predominantly from the body-wall muscles, contain two myosin isoforms and paramyosin as their major proteins. The two myosins are located in distinct regions of the surfaces, while paramyosin is located within the backbones of the filaments. Tubular structures constitute the cores of the polar regions, and electron-dense material is present in the cores of the central regions (Epstein, H.F., D.M. Miller, I. Ortiz, and G.C. Berliner. 1985. J. Cell Biol. 100:904-915). Biochemical, genetic, and immunological experiments indicate that the two myosins and paramyosin are not necessary core components (Epstein, H.F., I. Ortiz, and L.A. Traeger Mackinnon. 1986. J. Cell Biol. 103:985-993). The existence of the core structures suggests, therefore, that additional proteins may be associated with thick filaments in C. elegans. To biochemically detect minor associated proteins, a new procedure for the isolation of thick filaments of high purity and structural preservation has been developed. The final step, glycerol gradient centrifugation, yielded fractions that are contaminated by, at most, 1-2% with actin, tropomyosin, or ribosome-associated proteins on the basis of Coomassie Blue staining and electron microscopy. Silver staining and radioautography of gel electrophoretograms of unlabeled and 35S-labeled proteins, respectively, revealed at least 10 additional bands that cosedimented with thick filaments in glycerol gradients. Core structures prepared from wild-type thick filaments contained at least six of these thick filament-associated protein bands. The six proteins also cosedimented with thick filaments purified by gradient centrifugation from CB190 mutants lacking myosin heavy chain B and from CB1214 mutants lacking paramyosin. For these reasons, we propose that the six associated proteins are potential candidates for putative components of core structures in the thick filaments of body-wall muscles of C. elegans.